(untitled) (Research, Society and Development, 2021)
This study aimed to verify the occurrence and socio-environmental impacts of the presence of African Snail in the Açai neighborhood, city of Macapá, State of Amapá, showing problems such as the occurrence of the species and the lack of knowledge of the community about its infestation and control. The interviews were conducted using semi-structured forms to collect information on site and photographic record, for a period of four months (08/2013 to 12/2013). Variables of social and environmental axes were evaluated as impact indicators. The results showed that a greater performance of the public would contribute directly to the quality of life of the population and the environment, promoting the decrease in the occurrence of this snail. An environmental education program aimed at disseminating information on the impacts of African snail should be encouraged. It is necessary to work in the development of legal instruments, as well as in the development of campaigns to clarify the population.